2007
DOI: 10.1177/112067210701700509
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate for Uveitis Associated with Juvenile Idiopathic Arthritis: Value and Requirement for Additional Anti-Inflammatory Medication

Abstract: The data suggest that MTX is very effective in controlling inflammation of uveitis in patients with JIA. However, additional topical steroids or systemic immunosuppressive drugs are often required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 13 publications
3
41
0
9
Order By: Relevance
“…Therefore, as monotherapy and in combination with ETA or ADA, MTX seems to have a protective effect on the occurrence of uveitis. Previous open-label studies showed that MTX is an effective treatment for uveitis; approximately 60-70% of patients responded and had a longer remission rate while taking MTX (19,20), and it therefore seems to be protective toward the reoccurrence of uveitis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as monotherapy and in combination with ETA or ADA, MTX seems to have a protective effect on the occurrence of uveitis. Previous open-label studies showed that MTX is an effective treatment for uveitis; approximately 60-70% of patients responded and had a longer remission rate while taking MTX (19,20), and it therefore seems to be protective toward the reoccurrence of uveitis (21).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of methotrexate on JIA-associated uveitis has been reported in numerous case series [52][53][54][55][56][57][58][59].…”
Section: Treatment With Immunosuppressives and Biologicalsmentioning
confidence: 98%
“…Nine of them achieved inflammation control on MMF without concomitant corticosteroids or other IMTs for a median of 15 months (range: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. During this follow-up period, 8 out of the 9 patients experienced no uveitis relapse; 1 patient experienced one relapse that was treated with 4 weeks of topical corticosteroids.…”
Section: Treatment Outcomesmentioning
confidence: 99%